Discovering intuitive intelligence: real stories from personal and professional life - Brand, Colin G. (Henry Stewart Talks, 2019)
Intuitive intelligence, Leadership, Decision making, Mining industry, Military, Media industry, Career choices, Public service, Private sector, Entrepreneurship, Evidence-based practice